2006
DOI: 10.3892/or.15.4.875
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between chemosensitivity and mRNA expression level of 5-fluorouracil-related metabolic enzymes during liver metastasis of colorectal cancer

Abstract: Abstract. The attainment of chemoresistance during tumor metastasis is often experienced. In this study, we evaluated the correlation between sensitivity to 5-fluorouracil (5-FU) and the mRNA expression level of several 5-FU-related metabolic enzymes [thymidylate synthase, dihydropyrimidine dehydrogenase (DPD), thymidylate phosphorylase (TP), orotate phosphoribosyl transferase, and uridine phosphorylase] in primary colorectal cancer and synchronous liver metastases from ten patients to investigate how colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Although these investigations have previously been reported (16)(17)(18)(19)26,27), the results remain controversial. This discrepancy may be caused by the difference in methodology and study population.…”
Section: Synchronous Liver Metastasis (N=15) Metachronous Liver Metasmentioning
confidence: 56%
See 1 more Smart Citation
“…Although these investigations have previously been reported (16)(17)(18)(19)26,27), the results remain controversial. This discrepancy may be caused by the difference in methodology and study population.…”
Section: Synchronous Liver Metastasis (N=15) Metachronous Liver Metasmentioning
confidence: 56%
“…This discrepancy may be caused by the difference in methodology and study population. As for TS mRNA expression, almost all reports have demonstrated supportive results that there was not a significant alteration between primary tumor and liver metastatic tumor (17,19,26,27), while it has been reported that the TS mRNA levels in metachronous liver metastases were higher than those in primary tumors (18). This evidence led us to the conclusion that examining the TS mRNA level in primary colorectal cancer tissue as a predictive indicator of chemosensitivity is sufficient and it is not necessary to know the TS mRNA level in liver metastatic cancer tissue.…”
Section: Synchronous Liver Metastasis (N=15) Metachronous Liver Metasmentioning
confidence: 83%
“…Our data suggest a possible mechanism of initial low passage AT-MSC chemoresistance by the expression of DPD that contributed to 5FU catabolism [28]. TP expression in AT-MSC in combination with DPD has been ascribed to 5FU resistance [29].…”
Section: Discussionmentioning
confidence: 94%
“…Cells did not exhibit any morphological changes and were found not to be tumourigenic upon subcutaneous injection in nude mice (data not shown). The expression analysis of enzymes involved in 5FU metabolism and resistance [27,28] revealed that both low passage and high passage AT-MSC express thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD), thymidylate phosphorylase (TP), orotate phosphoribosyltransferase (OPRT) ( Figure 3A). However, expression of thymidylate phosphorylase TP (plateletderived endothelial cell growth factor; PD-ECGF) was not found in human fibroblasts.…”
Section: Characterization Of Therapeutic Cells CD Y -At-mscmentioning
confidence: 99%
“…Iwahashi et al reported that overall survival was significantly better in a chemosensitivity-guided chemotherapy group than in a standard chemotherapy or non-chemotherapy group in advanced gastric cancer (10). There have been several studies employing the chemosensitivity assay in ovarian cancer, breast cancer and leukemia (11)(12)(13)(14), while the number of studies using CD-DST in particular are increasing (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%